Organizational Ethics, Individual Ethics, and Ethical Intentions in International Decision-Making - Elango, Balasubramanian (Journal of business ethics, 2010)
This study explores the impact of both individual ethics (IE) and organizational ethics (OE) on ethical intention (EI). Ethical intention, or the individual’s intention to engage in ethical behavior, is useful as a dependent variable because it relates to behavior which can be an expression of values, but also is influenced by organizational and societal variables. The focus is on EI in international business decision-making, since the international context provides great latitude in making ethical decisions. Results demonstrate that both IE and OE influence EI. Ethical congruence is also discussed as a positive influence. Younger managers are more influenced by OE than older managers. The findings call for creating governance mechanisms to enhance ethical congruence, thereby increasing the likelihood of managers making ethical choices in organizational decision-making.